√x-1 + √2x + 6=6 (Квадратный корень над-1 и  6)

 √x-1 + √2x + 6=6 (Квадратный корень над-1 и  6)
Гость
Ответ(ы) на вопрос:
Гость
[latex] \sqrt{x-1} + \sqrt{2x+6} = 6 5 + 3x + 2 \sqrt{(x - 1)(2x + 6)} = 36 2 \sqrt{(x - 1)(2x + 6)} = 31 - 3x 4(x - 1)(2x + 6) = (31 - 3x)^2 8x^2 + 16x - 24 = (31 - 3x)^2 8x^2 + 16x - 24 = 9x^2 - 186x + 961 -x^2 + 202x - 985 = 0 -(x - 197)(x - 5) = 0 |*(-1) (x - 197)(x - 5) = 0 x - 197 = 0 ; x - 5 = 0 x = 197 ; x = 5 x = 5 [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы